2013
DOI: 10.1534/genetics.113.150581
|View full text |Cite
|
Sign up to set email alerts
|

Meiotic and Mitotic Recombination in Meiosis

Abstract: Meiotic crossovers facilitate the segregation of homologous chromosomes and increase genetic diversity. The formation of meiotic crossovers was previously posited to occur via two pathways, with the relative use of each pathway varying between organisms; however, this paradigm could not explain all crossovers, and many of the key proteins involved were unidentified. Recent studies that identify some of these proteins reinforce and expand the model of two meiotic crossover pathways. The results provide novel in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
82
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(85 citation statements)
references
References 64 publications
(72 reference statements)
3
82
0
Order By: Relevance
“…While it has been suggested that MutSg promotes COs primarily by antagonizing the functions of helicases that would dismantle CO intermediates (Kohl and Sekelsky 2013), we have found that in the context of C. elegans meiosis, the requirements for MutSg and its partner COSA-1 in chiasma formation are not bypassed by eliminating either HIM-6/BLM (this work) or RTEL-1 (Yokoo et al 2012). We suggest that instead of (or in addition to) antagonizing anti-CO helicases, MutSg and other pro-CO factors may be needed to antagonize inappropriate resolvase activities, to recruit appropriate resolvases, to recruit HIM-6/BLM, and/or to preserve the structure of the intermediates in a form that confers biased resolution.…”
Section: Him-6/blm Function In Promoting Meiotic Cosmentioning
confidence: 99%
See 1 more Smart Citation
“…While it has been suggested that MutSg promotes COs primarily by antagonizing the functions of helicases that would dismantle CO intermediates (Kohl and Sekelsky 2013), we have found that in the context of C. elegans meiosis, the requirements for MutSg and its partner COSA-1 in chiasma formation are not bypassed by eliminating either HIM-6/BLM (this work) or RTEL-1 (Yokoo et al 2012). We suggest that instead of (or in addition to) antagonizing anti-CO helicases, MutSg and other pro-CO factors may be needed to antagonize inappropriate resolvase activities, to recruit appropriate resolvases, to recruit HIM-6/BLM, and/or to preserve the structure of the intermediates in a form that confers biased resolution.…”
Section: Him-6/blm Function In Promoting Meiotic Cosmentioning
confidence: 99%
“…Recent evidence suggests that checkpoint-like feedback mechanisms operate to ensure both that DSB formation continues until each homolog pair has at least one CO-eligible recombination intermediate and that DSB formation will shut down once this condition is met Stamper et al 2013). Following DSB formation, a subset of the initial recombination intermediates is selected to become COs, recruiting a cohort of CO-promoting (pro-CO) proteins that function to stabilize and protect these COdesignated intermediates (Baudat and De Massy 2007;Kohl and Sekelsky 2013;Lynn et al 2007). A widely conserved solution for protecting potential CO intermediates involves the MutSg complex, comprising MSH4 and MSH5, meiosisspecific members of the MutS protein family that can form a sliding clamp on DNA in response to recognition of branched DNA structures (Baudat and De Massy 2007;Lynn et al 2007;Snowden et al 2004).…”
mentioning
confidence: 99%
“…The present model postulates two mitoticlike pathways (leading, respectively, to noncrossovers and crossovers [COs] that are not subject to chromosome interference), and one meiosis-specific pathway (leading to COs that are subject to chromosome interference) (e.g., Kohl and Sekelsky 2013). Many genes have been identified that, upon mutation, affect meiotic recombination.…”
mentioning
confidence: 99%
“…Since that time, a great deal has been learned about the functions, molecular mechanisms, and regulation of meiotic recombination. This process is initiated through the introduction of programmed DNA doublestrand breaks (DSBs), which are then repaired through highly regulated homologous recombination (HR) pathways such that a substantial fraction of repair events produce reciprocal crossovers (reviewed in Kohl and Sekelsky 2013). The chiasmata that form at sites of crossovers help to ensure accurate segregation of homologous chromosomes.…”
mentioning
confidence: 99%